Hop on Pop - Geisel, Theodor Suess Dr. (New York Random Hose, 1991)
Pairs of rhyming words are introduced and used in simple sentences, such as "Day. Play. We play all day. Night. Fight. We fight all night."
D
On board pages.
b
b
Keywords: Stories in rhyme